The princess twins and the birthday party - Hodgson, Mona; Olson, Julie (Grand Rapids, Michigan : Zonderkidz, 2016)
"Princesses Abby and Emma are ready to celebrate their birthday with their friends. But where did Beth go? Can Emma convince Beth to come back to the party?"--Cover.
Keywords: Children's stories